Kepuasan Konsumen Sebagai Dampak dari Relationship Marketing dan Kebijakan Harga - Nursatriani; Norhaedah; Ernawati; Nugraha Abhull Azwad (LPPM STIEM BONGAYA, 2025)
The research conducted aims to identify the influence of promotion and service quality partially, as well as identify the simultaneous influence of promotion and service quality on purchasing decisions at the Mario Cell Pammanu Store, Luwu Regency. The time of this research is approximately 3 months from May to July 2025. This research applies a quantitative method whose population utilizes customers of the Mario Cell Pammanu Store. The sample used is 96 people based on the lemeshow formula in determining the sample. The instrument tests used are validity testing, reliability testing, linear multiple regression testing, while the classical assumption tests used are normality testing, multicollinearity testing, heteroscedasticity testing, and hypothesis testing applied is t testing (partial hypothesis testing), f testing (simultaneous hypothesis testing), as well as determination testing using SPSS version 31. The final findings of this research prove that promotions have a partial influence on purchasing decisions which produces a t count of 3.121 with a sig level of 0.003. Service quality also has a partial effect on purchasing decisions, resulting in a t-value of 3.620 with a significance level of <0.001. Simultaneously, these two independent variables influence purchasing decisions, resulting in an F-value of 47.559 with a significance level of <0.001.Keywords: Promotion, service quality, purchasing decisions.